The effectiveness of treatment based on parent management training on psychological well-being and quality of life of mothers of children with attention deficit and hyperactivity disorder - Narimani, Nilofar; Najdi, Leila; pourtaleb, narges (Psychology of Woman Journal, 2022)
Problems related to caring for children with attention deficit hyperactivity disorder (ADHD) can expose parents, especially mothers, to the risk of mental health problems. Few research pieces of evidence have addressed the role of educating parents and improving their psychological health in this disorder. Therefore, this research aimed to investigate the effectiveness of treatment based on parent management training on the psychological well-being and quality of life of mothers of children with ADHD. The current research is a field experiment with a pre-test-post-test design. Thirty mothers of children with ADHD were selected by available and targeted sampling methods in one of the special treatment centers for these children and randomly assigned to two experimental and control groups. At the beginning and end of the research, two groups were interviewed and answered the questionnaire on psychological well-being and quality of life. The experimental group was subjected to treatment intervention based on parent management training during nine sessions, one session per week. The results of ANCOVA analyses showed that the treatment based on parent management training was effective in increasing the psychological well-being score and the quality of life score of mothers of children with ADHD in the experimental group compared to the control group. It seems that by using treatment measures based on parent management training and generalizing it to different social contexts, it is possible to improve the management skills of mothers in interacting and caring for children with ADHD. It can be helpful as a potential capacity to increase psychological well-being and their quality of life in daily life.